Study of Sunspot Effect on Radio Jove Telescope Observation - Abood, Kamal; Ebadi, Noor (Iraqi Journal of Science, 2023)
In this research, study the effect of sunspots on electromagnetic radio signals when it passed through F layer. The evaluation for this effect is carried out on radio Jove telescope frequency (20.1MHz) observations result. Radio emission for Jupiter storm burst observations over 11 years (1999-2009) from Hawaii, USA station (about 37611observations must be attended), are used in this research.Two data limitations are applied on number of observation for Hawaii station, first due station location, second due to the reception of telescope antenna. The number of observations are reduced to 337 due to these limitation, but the actual number that be detected by station telescope is only 20.A model for ionospherical effect ,only due to sunspot number in observation day, is achieved in this paper. The behavior of this effect depending on actual observations (20 observations) is represented by polynomial equation of order degree three. The range of K sunspot value according the effect curve representation is determined by difference calculation between actual observation day sunspot number and the sunspot number must be to achieve the model curve this range is 2